Kinship affinity in the domestic partnership - Posadas Gutiérrez, Rose Mary (2018)
According to article 237° of the Civil Code, marriage produces kinship by affinity between each of the spouses with the blood relatives of the other; being in the same line and degree of kinship by affinity that the other spouse by consanguinity; but what happens in the domestic partership regulated and protected also by the Political Constitution and the Civil Code itself? Is there also generated or should there be kinship by affinity? Through this article, we will analyze the institution of kinship, specifically kinship by affinity, its purpose and its relation to the concept of family from the constitutional framework, to determine its scope to the domestic partnership. In this sense, affinity is analyzed as a cause of kinship, coexistence and its relationship with the Theory of Impediments, the protection the domestic partership as sources of family generation; to finally evaluate the extent of affinity to these unions.